(untitled) (Siddhajyoti Interdisciplinary Journal, 2021)
Home and human rights appear as interwined categories in narratives related to migration. However, these two categories have not been amply explored as proximate matters in any migration related texts such as Registän Diary. Home is not only a place for dwelling with varying frameworks but also many other things like a space, a feeling and a will to belong. Having a home, a place to dwell and belong, is one of the basic rights of human, specifically in line with the view that human rights are rights held by individuals simply because they are part of the human species regardless of their sex, race, nationality, and economic background. In this paper, the researcher, remaining within the paradigm of qualitative research, draws ideas from the scholars alike Pico Iyer, Salman Rushdie, Shalley Mallet, Lynn Hunt, Joseph R. Slaughter, examines the life narratives of the labour migrants to the Gulf from Nepal, argues and concludes that be it through the multifaceted depiction of home or cases of human rights abuse, Registän Diary negotiates a free belonging for all the citizens in a secure world.